Sarah Lionti S. Pd - Sarah Lionti; Jajang Rahmatudin; sumliyah sumliyah (Integral : Pendidikan Matematika, 2021)
This study aims to determine how the development of mathematics learning videos for Cartesian coordinate material assisted by YouTube social media as an alternative learning for students of SMP Negeri 1 Tengah Tani. The resulting YouTube social media assisted mathematics learning video has been developed with the Borg & Gall (1983: 775) model modified by Sugiyono (2017: 409). This study produces a mathematics learning video of Cartesian coordinate material assisted by YouTube social media as an alternative learning with the results of the assessment of material experts with an average score of 3,60 results from the curriculum experts with a score of 3.60 results from media experts with a score of 4.00 and the results of teaching teacher with an average score of 3.70 thus producing learning media with criteria "very valid". Products that have been validated by experts are then tested on students by filling in a response questionnaire to determine the level of attractiveness of the learning videos that have been developed and get an average score of 3.58 with the criteria "very interesting". Keyword : Research & Development, Learning Videos, Cartesian coordinates.